1984
DOI: 10.1038/311752a0
|View full text |Cite
|
Sign up to set email alerts
|

Insertion of N regions into heavy-chain genes is correlated with expression of terminal deoxytransferase in B cells

Abstract: The variable regions of immunoglobulin heavy chains are encoded in the germ line by three discrete DNA segments: VH (variable) elements, D (diversity) elements and JH (joining) elements. During the differentiation of B lymphocytes, individual segments from each group are brought together by recombination to form the complete VHDJH variable region. To understand these processes better, we have now isolated and sequenced molecular clones representing intermediates (DJH fusions) and final products (VH-to-DJH join… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
231
0
2

Year Published

1992
1992
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 499 publications
(238 citation statements)
references
References 33 publications
5
231
0
2
Order By: Relevance
“…These extra nucleotides may be the result of de novo N-additions or an unusual rearrangement resulting from the use of nucleotides from the non-coding germ-line 3 0 end of the V gene, 5 0 end of the J and P-additions [38]. Earlier studies of the incidence of N-addition had shown that the process is associated with the activity of the TdT enzyme, which was thought to be active only in pre-B cells before the production of functional heavy chains [44]. In human V genes, N-additions were mainly seen in abortive V -J rearrangements or in translocations involving the light locus, suggesting that TdT activity may occur in certain B cells at the stage of development when the rearranging machinery proceeds to the locus [45].…”
Section: Discussionmentioning
confidence: 99%
“…These extra nucleotides may be the result of de novo N-additions or an unusual rearrangement resulting from the use of nucleotides from the non-coding germ-line 3 0 end of the V gene, 5 0 end of the J and P-additions [38]. Earlier studies of the incidence of N-addition had shown that the process is associated with the activity of the TdT enzyme, which was thought to be active only in pre-B cells before the production of functional heavy chains [44]. In human V genes, N-additions were mainly seen in abortive V -J rearrangements or in translocations involving the light locus, suggesting that TdT activity may occur in certain B cells at the stage of development when the rearranging machinery proceeds to the locus [45].…”
Section: Discussionmentioning
confidence: 99%
“…It is not possible to tell whether such breaks are single or double stranded. Although TdT is able e¤ciently to tail single-stranded DNA in vitro (Sambrook et al 1989) and can probably tail a nicked template (Grawunder & Lieber 1997), its only known in vivo action is the tailing of double-strand breaks during V(D)J recombination (Alt & Baltimore 1982;Desiderio et al 1984;Landau et al 1987). In vitro studies suggest that this action on doublestrand breaks is less e¤cient if the break is £ush or has a recessed 3'-end (Bollum 1974).…”
Section: Dna Breaks In Hypermutation and Isotype Switchingmentioning
confidence: 99%
“…This conundrum was elegantly answered many years ago by an expansion of the primary Ab repertoire through genetic recombination of VDJ gene segments and by resultant combinatorial diversity arising from rearranged heterodimers of light and heavy chains (1). Recent high-throughput sequencing data in zebra fish and humans have provided further insights into the extent of the expressed Ab repertoire, as envisaged by Tonegawa et al (2,3) However, quantitative assessment, even after considering other possible mechanisms, proves this diversity to be inadequate for recognition of infinite Ags (4).…”
mentioning
confidence: 99%